1996
DOI: 10.1111/j.1365-2125.1996.tb00151.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repeated dermal application of capsaicin to the human skin on pain and vasodilatation induced by intradermal injection of acid and hypertonic solutions

Abstract: 1 The effect of repeated capsaicin application on the skin of the volar surface of the forearm on the pain sensation and on the increase in blood flow induced by intradermal injection of low pH media or hypertonic solutions was investigated in 13 healthy volunteers. 2 Low pH media (4, and 2.5) were obtained by adding HCl to 0.9% saline.Hypertonic solutions (300 and 600 mM) were obtained by adding NaCl to pH 7.4, 0.9% saline. Capsaicin (1% in 50% ethanol) was painted on the volar skin of one forearm, chosen at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The advent of an X-Y scanning laser probe now allows a more reliable method for characterizing the microvascular changes leading to the flare reaction [24]. Laser Doppler perfusion imaging has been used to study the influence of topically applied capsaicin on blood flow responses in the human skin [25]. Furthermore, Hershey et al used topical application of capsaicin on the skin of nonhuman primates and rats to stimulate CGRP-mediated vasodilation, which was measured by laser Doppler perfusion imaging [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of an X-Y scanning laser probe now allows a more reliable method for characterizing the microvascular changes leading to the flare reaction [24]. Laser Doppler perfusion imaging has been used to study the influence of topically applied capsaicin on blood flow responses in the human skin [25]. Furthermore, Hershey et al used topical application of capsaicin on the skin of nonhuman primates and rats to stimulate CGRP-mediated vasodilation, which was measured by laser Doppler perfusion imaging [26].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of an X‐Y scanning laser probe now allows a more reliable method for characterizing the microvascular changes leading to the flare reaction [24]. Laser Doppler perfusion imaging has been used to study the influence of topically applied capsaicin on blood flow responses in the human skin [25]. Furthermore, Hershey et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented in humans that capsaicin is a potent stimulant and nociceptors can become desensitized following repeated capsaicin applications [8][9][10] while a period of one week may not be adequate to wash out the effect of desensitization. 1,7,15 Although the underlying mechanism of capsaicin desensitization is not fully understood and difficult to assess given the lack of relationship between morphological changes in sensory neurons and the reversibility of the observed desensitization, it appears excitation of sensory neurons, cation influx and neuropeptide release in addition to capsaicin-operated cation channel may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…While mechanisms of desensitization of nerve fibers are not entirely understood, repeated capsaicin exposure can result in a period of refractoriness in which the nerve becomes irresponsive toward capsaicin or even other stimuli. [8][9][10] In humans, it has been reported that frequent applications of capsaicin for extended periods could diminish vasodilation. 9,11 Consequence of desensitization can be detrimental to reproducibility depending on the study design.…”
mentioning
confidence: 99%
“…These effects can be divided into medium- and long-term effects. Immediately after application, a painful burning sensation and hyperaemia may occur [27,28]. When higher doses are used for the treatment of neuropathic pain, a significant reduction of discomfort can be observed that cannot solely be explained by the direct pharmacological effects of capsaicin [29,30].…”
Section: Introductionmentioning
confidence: 99%